PELATIHAN MANAJEMEN ASET TETAP DAN PENYUSUTAN ASET TETAP UNTUK KEBERLANGSUNGAN USAHA PADA KOMUNITAS PETAMBAK PERINTIS DESA LONGOS SUMENEP - Ghufrony, Ahmad; Ainun, Moh. Baqir; Pitaloka, Diah Anggraeni; Harmanto, Stevan Ariputra (Lembaga Penelitian dan Pengabdian kepada Masyarakat - Universitas Abdurachman Saleh Situbondo, 2024)
Fixed assets are assets that a company definitely needs to run its business. Recording the acquisition of fixed assets and calculating depreciation of fixed assets is important to do correctly. This is because recording fixed assets and depreciation charges on fixed assets will affect the company's profit and loss. If the company makes a mistake in recording and calculating depreciation of fixed assets, the resulting profit and loss calculation will also be wrong. Business owners will think that their business is making a profit, even though if the depreciation of fixed assets is recorded and calculated correctly, it is likely that the business will actually experience a loss. If this type of misinformation is left unchecked, it will have an impact on the development and sustainability of the business. Such problems occurred in the